Presentation and Management of soft tissue Foreign Bodies The most challenging surgeries - Dr Pradeep BALMIKI, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Accidental penetrating injuries with foreign bodies are a common presentation in hospital's emergency rooms. If missed, these bodies can remain dormant or result in a wide range of complications. This study evaluated the characteristics of patients, presentation and management who suffered foreign body embedded in soft tissue at a ABV Government Medical College Vidisha MP India. Methods: The study was conducted at Department of surgery, Atal Bihari Vajpeyi Government Medical College Teaching Hospital from January 2021 to November2024. All cases confirmed to have a foreign body in soft tissue were enrolled.